Chapter Analysis of the theoretical settlement scenario implemented by the municipal plans. the case study of the Romagna coast municipalities - Zullo, Francesco (Proceedings e report, 2020)
In Italy, the transformative predictions of the municipal urban planning instruments are very often far away from the socio-economic dynamics. In fact, the political component considers the oversizing of urban transformative projections as a solution to improve the situation of the territories in crisis for several aspects. This work analyses the projections of the urban planning instruments in force in the coastal municipalities of Emilia-Romagna. The work aims to highlight how the planned urban areas can change the future settlement structure in the case study area.